The high‑resolution bathymetric dataset of the Saudi Arabian Red Sea margin from the 2022 Red Sea Decade Expedition - Marchese, Fabio; Nolan, Megan; Dunn, Natalie; Watts, Marta; von Krusenstiern, Katherine; Foy, Craig; Rodrigue, Mattie; Pieribone, Vincent; Qurban, Mohammed; Duarte, Carlos; Benzoni, Francesca (European Organization for Nuclear Research, 2026)
Gridded multibeam bathymetry of the Saudi Arabian Red Sea collected during the 2022 Red Sea Decade Expedition (funded by the National Center for Wildlife, Kingdom of Saudi Arabia). The QPS Qimera software license was provided by King Abdullah University of Science and Technology (KAUST) through baseline funding awarded to Francesca Benzoni (BAS/1/1090-01-01). The dataset includes one 40 m resolution model covering the full deep-water survey area, acquired by the Kongsberg EM 304 aboard the M/V OceanXplorer (OCX), and four 5 m resolution models of shallow-water bathymetry acquired by the Teledyne RESON SeaBat T50-P aboard Metalshark38 (MS), one per expedition Leg (L1 to L4).
Publication Title: Zenodo (CERN European Organization for Nuclear Research)
Keywords: Bathymetry; High resolution; Indian ocean; License; Margin (machine learning); dept.egm